Date Palm Cultivation, Consumption and Export: Current Status and Future Challenges - A Review - Solangi, Najamuddin; Abul-Soad, Adel Ahmed; Jatoi, Mushtaque Ahmed; Mirani, Abdul Aziz; Markhand, Ghulam Sarwar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The date palm is an important horticultural crop, cultivated in all provinces of Pakistan, particularly in Khairpur and Sukkur districts of Sindh. Khairpur is biodiversity center for dates, with cultivation of elite commercially important cultivars like Aseel (predominant cultivar), Karbalain, Otakin, Kurh, Dedhi, Dhakki, Kashuwari, Kupro and Fasli etc. Aseel dates are consumed locally as table dates as well as exported to Germany, USA, Canada and Japan in the form of pitted and chopped dates by the different dates factories established in the country. Most of the Aseel dates are exported to India as yellow and brown chhuhara (boiled dried dates). Dates are also used to make different value-added products (date syrup, date paste, date pickles, date bars, date powder, date extracts, date jam). Poor pre- and post-harvest management and poor cultural practices are major obstacles in obtaining dates of international standards. Currently, date palms in Sindh face the effects of natural disasters, i.e., floods, post-flood diseases (sudden decline disease in the crown caused by Fusarium solani), and pests, such as, Red Palm Weevil (Rhynchophorus ferrugineus). Multiplication of elite and rare date palm cultivars by tissue culture technique is pre-requisite for large-scale cultivation which may fill the gap of destruction of indigenous date palm cultivars. Currently, thousands of grown-up trees of date palm have been destroyed with post-flood sudden decline disease. Proper pre- and post-harvest management and cultural practices and in addition cultivation of disease resistant cultivars are need of the time. In this review article, different aspects of date palm problems have been discussed and their solutions are suggested to benefit the date palm growers who can manage the crop in a better way.